Trends of leptospirosis cases in a tertiary care center in Northern Kerala during January 2013 to October 2019 - Sanya, Rameela; Kumaran, Jayasree Anandabhavan (International Journal Of Community Medicine And Public Health, 2020)
Background: Leptospirosis is a zoonosis endemic in tropical climates. Though overall incidence of leptospirosis has decreased during recent years, it continues to be a major public health problem, highly underreported in India. Various trends such as seasonal, geographical, mortality have to be studied in detail for proper planning of prevention and control programs. The objective of this study was to assess geographical, seasonal, mortality trends of leptospirosis cases attending a tertiary care centre in Northern Kerala, from January 2013 to October 2019. Methods: A record-based retrospective study was conducted where leptospirosis cases attending tertiary care centre were included. Data was entered into Microsoft Excel 2007, analysed using Epi Info 7. Results were expressed as frequencies, percentages. Results: Among 647 leptospirosis cases, 141 were confirmed and 506 were probable. Maximum number of cases were reported in 2014 and maximum deaths were reported in 2019. Majority belonged to 51-60 years age category; males outnumbered females. Maximum cases were reported during September, August. Major hotspots for leptospirosis were Kannur and Taliparamba Municipalities and Koothuparamba. Conclusions: During rainy season, probably younger individuals are at risk as they indulge in leisure like swimming, playing while post rainy season older individuals are at risk due to occupational exposure. The number of deaths showed a declining trend from 2013 to 2018, but increased in 2019. Few of the previous hotspots reported decline in cases probably due to improved surveillance and control activities.